Three new succinate-phenolic conjugates from the fruits of Actinidia arguta. (April 2022) - Ahn, Jong Hoon; Yeon, Sang Won; Ryu, Se Hwan; Lee, Solip; Turk, Ayman; Hwang, Bang Yeon; Lee, Mi Kyeong
Graphical abstract: Highlights: Three undescribed compounds, argutinoosides J–L, were isolated from Actinidia arguta . The structures were elucidated as succinate conjugated phenolic glycosides. Compounds 1 and 2 showed antioxidant activity. Abstract: The fruit of Actinidia arguta, also called kiwiberry or hardy kiwifruit has cold-resistant characteristics with diverse biological activities. In this study, investigations was carried out to characterize the bioactive constituents of A. arguta for the elucidation of its health beneficial properties. Three new succinate conjugated phenolic glycosides, namely argutinosides J–L (1 -3 ) were isolated from the fruits of A. arguta . The structures were determined on the basis of combined spectroscopic analysis by IR, UV, HRESIMS, 1D and 2D NMR spectral analysis. Compounds 1 and 2 showed mild DPPH radical scavenging activity by 52.1 % and 68.2 %, respectively, at the concentration of 500 μM whereas compound 3 showed weak activity.